(3GdfcJ GdhajI HTQM GdechOj Ydi GdCdajIs - (3eMeO (B((3CHhQGS(B) (3CMeO Hf GdfGUQ, GdfGUQj GdLQHjs; (3GdechOj (B- (3GdeWQRj,J (B807 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd eMeO CHhQGS Hf GdfGUQ hcGf Yde GdfMh efgG hSjdI dcd ebUhO s
(3BNQgG (B:s
(3aEf bdJ(B: (3gd jLhR bdHgG aj dZI ef GdJRegG eWdbkG? bdJ(B: (3bGd aj GdGQJTGa ced GdLRA GdChd s
(3HgG fXGe GdJYbjHIs
(3HChdgG WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B156 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B529s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B336 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs